Germination alters the microstructure, in vitro protein digestibility, α‐glucosidase and dipeptidyl peptidase‐IV inhibitory activities of bioaccessible fraction of pigeon pea (Cajanus cajan) seeds. Issue 1 (24th February 2021) - Ohanenye, Ikenna Christian; Sun, Xiaohong; Sarteshnizi, Roghayeh Amini; Udenigwe, Chibuike C.
Abstract: Germination was investigated as a bioprocess for enhancing the digestibility and bioactivity of pigeon pea ( Cajanus cajan ). Pigeon pea seeds were germinated for 0, 4, 24 and 48 h. Electrophoresis revealed that the 7S vicilin subunits were the most abundant proteins in control and germinated seeds. FTIR showed a loss of β sheet and a gain of α‐helix contents, and microscopy showed cell wall degradation in germinated seeds. Germination decreased the seed protein yield due to partial hydrolysis of proteins. After in vitro digestion, 48‐h germination increased the protein digestibility‐corrected amino acid score of the pigeon pea flour and isolated protein. Germination also enhanced the inhibitory activity of the seed digesta against α‐glucosidase but not dipeptidyl peptidase IV. Taken together, germination could be used to enhance the nutritional quality and bioactivity of pigeon pea towards improving its future utilization as novel healthy food for mitigating food insecurity.